2018
DOI: 10.1080/09638288.2018.1480667
|View full text |Cite
|
Sign up to set email alerts
|

Can scuba diving offer therapeutic benefit to military veterans experiencing physical and psychological injuries as a result of combat? A service evaluation of Deptherapy UK

Abstract: Scuba diving can offer significant therapeutic benefits, particularly for ex-military amputees experiencing co-morbid anxiety and/or chronic psychological adjustment disorders, notably in terms of improvements in social dysfunction and symptomology of depression. Implications for Rehabilitation Scuba Diving as a Therapy Military combat can result in devastating, chronic physical and/or psychological injury. Current research suggests that a combination of medical and psychological therapy may prove to be the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 16 publications
2
35
0
2
Order By: Relevance
“…It can also be seen in the number of divers who participated in the study (64 people) as compared to non-divers ( n = 118). The groups of divers examined in studies carried out by other authors were also small [ 9 , 20 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can also be seen in the number of divers who participated in the study (64 people) as compared to non-divers ( n = 118). The groups of divers examined in studies carried out by other authors were also small [ 9 , 20 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biggest group in the present study comprised people suffering from motoric dysfunctions, which were the main reason for the disabilities. In the majority of published studies concerning the diving of people with disabilities, the studied group was also composed of people whose disability resulted from dysfunctions of the locomotor system, such as paraplegic divers [ 7 , 26 ], war veterans [ 6 , 27 ] or people after limb amputations [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a study carried out on veteran soldiers undertaking diving programs with Deptherapy UK reported an overall improvement in psychosocial wellbeing scores after scuba diving therapy ( N = 15), including decreased levels of anxiety, insomnia, and depression. Variables were measured using the quantitative 28-Scale General Health Questionnaire and personalized interviews [ 28 ]. Deptherapy UK is the first initiative in the world to use scuba diving as therapy and offers specially adapted scuba diving courses for seriously injured veterans of the British Armed Forces, presenting them new mental and physical challenges and empowering them to overcome their illnesses [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…While in-depth exploration of water-based physical activities are outside the auspices of this review, a couple of novel applications of immersive water-based activities are worth noting. A recent study evaluated Deptherapy, a UK-based charity that provides a scuba diving intervention as support to military veterans who experienced life-changing injuries from combat (64). A total of 15 male veterans were assessed in an uncontrolled format both prospectively and retrospectively on a range of quantitative measures of mental well-being and functional ability outcomes.…”
Section: Watermentioning
confidence: 99%